+0  
 
0
217
1
avatar

n - (-5) =35

Guest Oct 24, 2017
 #1
avatar+349 
+1

\(n-(-5)=n+5\). When subtracting negative integers, you add them, as \(a-(-b)=a+(-1)(-b)=a+b\).

Doing that, we get \(n+5=35\)\(n=30\)laugh

Mathhemathh  Oct 24, 2017

11 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.